Ação antimicrobiana e antibiofilme do levamisol contra bactérias isoladas da orelha de cães com otite externa - Soares, Ana Carla de Castro Freitas (2023)
Canine otitis externa is one of the most common multifactorial diseases with possible microbiological involvement in the dermatological routine. There is currently a challenge to find alternative or auxiliary methods to conventional topical treatment in order to avoid the spread of microbial resistance. Levamisole is known for its anthelmintic and immunomodulatory action, but its antimicrobial potential has not yet been well characterised. Therefore, the aim of this study was to evaluate the antibacterial and antibiofilm effect of levamisole against strains isolated from dogs with otitis. To this end, 49 isolates from external ear canal collections were used, identified and antimicrobial sensitivity tests carried out. Sensitivity to levamisole in its planktonic form was assessed using broth microdilution, and 10 concentrations were tested, ranging from 0.036-18.75 mg/ml, to obtain the minimum inhibitory concentration (MIC). For biofilm formation, levamisole was tested at three concentrations: MIC, MIC/2and MIC/8, at intervals of 48 h, 72 h, 96 h and 120 h. Finally, the activity of levamisole on the mature biofilm was also assessed by broth microdilution, with 10 concentrations tested in the range 0.036-18.75 mg/ml. The minimum inhibitory concentrations (MICs) of levamisole against the isolates ranged from 0.58-2.34 mg/mL. Levamisole reduced biomass formation with a MIC of 1.17 mg/ml for all the isolates, up to a period of 120 hours (P<0.05). With regard to the mature biofilm, a significant reduction (P<0.05) in its biomass was observed at concentrations of 1.17 to 18.75 mg/ml of levamisole. Both in the action on the biofilm in formation and on the mature biofilm, levamisole showed more effective results against Gram-positive bacteria; however, it also showed results against Gram-negative bacteria, proving its broad- spectrum effect. Therefore, levamisole has shown promise as an alternative for the treatment of bacterial otitis in dogs.